2020
DOI: 10.3390/s20133807
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Differences in Fixation Pattern on a Companion Robot

Abstract: Recent studies have addressed the various benefits of companion robots and expanded the research scope to their design. However, the viewpoints of older adults have not been deeply investigated. Therefore, this study aimed to examine the distinctive viewpoints of older adults by comparing them with those of younger adults. Thirty-one older and thirty-one younger adults participated in an eye-tracking experiment to investigate their impressions of a bear-like robot mockup. They also completed interviews… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…In both the first and second experiments, the senior group tended to gaze at the robot's facial area for a longer duration than the control group. It was observed that the senior group, compared to the control group, showed a more prolonged gaze at the robot's facial area, concentrating their attention on the facial region rather than other areas of the robot (Table 6, Figure 9) [8]. Based on the experiments conducted prior to the eye-tracking experiment for prototype development, seniors showed a preference for teddy bear-like robots.…”
Section: Eye-tracking Experiments and Appearancementioning
confidence: 98%
See 1 more Smart Citation
“…In both the first and second experiments, the senior group tended to gaze at the robot's facial area for a longer duration than the control group. It was observed that the senior group, compared to the control group, showed a more prolonged gaze at the robot's facial area, concentrating their attention on the facial region rather than other areas of the robot (Table 6, Figure 9) [8]. Based on the experiments conducted prior to the eye-tracking experiment for prototype development, seniors showed a preference for teddy bear-like robots.…”
Section: Eye-tracking Experiments and Appearancementioning
confidence: 98%
“…The role of robots is becoming increasingly important as technology supports the daily lives of seniors, leading to studies on this topic. Service experiences have been designed based on prior studies that focus on understanding the issues related to the usability, safety, and sensibility of robots while considering the physical and cognitive aging as well as emotional characteristics of seniors [3][4][5][6][7][8]. In particular, digital companion robots that perform various roles, such as emotionally communicating with seniors and taking necessary measures in emergency cases, are anticipated as service robots that will become a key necessity in the future.…”
Section: Introductionmentioning
confidence: 99%
“…The user experience focuses on the cognitive, socio-cognitive and affective aspects that a person experiences when engaging with the robot, such as enjoyment, aesthetics and a desire for repeated use [71]. A recent study pointed that older persons are impressed with a robot that having physical attractiveness and social likeability [72].…”
Section: Companion and Service Combo Robotmentioning
confidence: 99%
“…Robot attributes that affect user experience have also been studied extensively, including the robots' appearance, behavior, and functionality. Whereas users expressed a preference for clear distinction between humans and robots in terms of physical appearance (Walden et al, 2015), they tended to favor those who looked more like humans (Khosla et al, 2012), or displayed human-like features and gestures (Caleb-Solly et al, 2014), and focused significantly more on the robot's face and paid less attention to the rest of the body (Oh & Ju, 2020). In terms of behavior, users wanted robots to be social, intelligent, and spontaneous (Frennert et al, 2017;Tulsulkar et al, 2021), although there was some incongruity regarding the robots' playfulness.…”
Section: Human-robot Interaction (Hri) In Later Lifementioning
confidence: 99%